2017
DOI: 10.1093/annonc/mdx332
|View full text |Cite
|
Sign up to set email alerts
|

Whole brain radiotherapy after stereotactic radiosurgery or surgical resection among patients with one to three brain metastases and favorable prognoses: a secondary analysis of EORTC 22952-26001

Abstract: NCT00002899.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 20 publications
3
33
0
1
Order By: Relevance
“…However, a second exploratory analysis of the EORTC 22952 trial did not replicate a survival advantage with WBRT among NSCLC patients with favorable DS-GPA scores at baseline or controlled extracranial disease. (9) Our results are similarly consistent with a lack of appreciable survival benefit with WBRT among patients with favorable prognoses, although intracranial control was improved with adjuvant WBRT. Salvage therapy, which was more frequent among the SRS alone group, may be responsible for the lack of a survival advantage in patients who received WBRT.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, a second exploratory analysis of the EORTC 22952 trial did not replicate a survival advantage with WBRT among NSCLC patients with favorable DS-GPA scores at baseline or controlled extracranial disease. (9) Our results are similarly consistent with a lack of appreciable survival benefit with WBRT among patients with favorable prognoses, although intracranial control was improved with adjuvant WBRT. Salvage therapy, which was more frequent among the SRS alone group, may be responsible for the lack of a survival advantage in patients who received WBRT.…”
Section: Discussionsupporting
confidence: 84%
“…(6, 7) Whereas a secondary analysis of the JROSG-99 trial had demonstrated an overall survival benefit to WBRT among lung cancer patients with favorable diagnosis-specific graded prognostic assessment (DS-GPA) scores(8), an exploratory analysis of the EORTC 22952 trial found no such benefit. (9) In consequence of the persistent, conflicting evidence related to the effect of WBRT on survival in patient sub-populations, we sought to evaluate outcomes of non-small cell lung cancer (NSCLC) patients according to the receipt of WBRT and DS-GPA score within the North Central Cancer Treatment Group N0574 (Alliance) trial.…”
Section: Introductionmentioning
confidence: 99%
“…Their data demonstrated that median overall survival was not significantly different between both groups (10.7 months vs 10.9 months; p = 0.89). More recently a second analysis was performed and showed similar results: Churilla et al compared limited BM 1 to 3 vs extended BM (> 3) and concluded that number of BM treated by SRS was not associated to overall outcome [22]. Patients with multiple BM were more likely to have extracranial progression.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, even if these scores systems have been validated, they were developed based on patients treated by WBRT and not by SRS or HFSRT alone [13,24]. Each score refers to different predictive factors such as age, BM number, histology of primitive tumor and performance status score [22,25]. Nieder et al suggested that all these criteria can not be reported in some clinical situations [26].…”
Section: Discussionmentioning
confidence: 99%
“…9 These trials establish the role of postoperative SRS for resected BMs; however, the suboptimal local controls with postoperative SRS in these studies (72% and 61%) underscore efforts to optimize SRS dose, fractionation, and technique in the postoperative setting. 47 Secondary analyses of the data set from the EORTC 22952 showed no OS benefit with addition of WBRT irrespective of extracranial disease status or NSCLC prognostic group 48 and provide a counterpoint to a prior JROSG-991 analysis suggesting improved OS with WBRT in these patients. 49 An update of the JLGK-0901 prospective study of SRS alone for one to 10 BMs demonstrated good cognitive preservation and low rates of SRS toxicity.…”
Section: Bmsmentioning
confidence: 96%